The association between area-level residential instability and gray matter volume changes. (1st June 2022) - Ku, B.; Addington, J.; Bearden, C.; Cadenhead, K.; Cannon, T.; Compton, M.; Cornblatt, B.; Druss, B.; Keshavan, M.; Mathalon, D.; Mcglashan, T.; Perkins, D.; et al.
Abstract : Introduction: Area-level residential instability (ARI), an index of social fragmentation, has been shown to explain the association between urbanicity and psychosis. Urban upbringing has been shown to be associated with decreased gray matter volumes (GMV)s of brain regions corresponding to the right caudal middle frontal gyrus (CMFG) and rostral anterior cingulate cortex (rACC). Objectives: We hypothesize that greater ARI will be associated with reduced right posterior CMFG and rACC GMVs. Methods: Data were collected at baseline as part of the North American Prodrome Longitudinal Study. Counties where participants resided during childhood were geographically coded using the US Censuses to area-level factors. ARI was defined as the percentage of residents living in a different house five years ago. Generalized linear mixed models tested associations between ARI and GMVs. Results: This study included 29 HC and 64 CHR-P individuals who were aged 12 to 24 years, had remained in their baseline residential area, and had magnetic resonance imaging scans. ARI was associated with reduced right CMFG (adjusted β = -0.258; 95% CI = -0.502 – -0.015) and right rACC volumes (adjusted β = -0.318; 95% CI = -0.612 – -0.023). The interaction terms (ARI X diagnostic group) in the prediction of both brain regions were not significant, indicating that the relationships between ARI and regional brain volumes held for both CHR-P and HCs. Conclusions: Like urban upbringing, ARI may be an important social environmental characteristic that adversely impacts brain regions related to schizophrenia. Disclosure: No significant relationships.